(3fgGjI GdCQH ef PcQ hdGI MdHs - (3CMeO Hf eMeO Hf Ydj GdMUcaj, GHf GdedG ,J (B1003 (3g` s
(3ChdgG (B:s
(3Chd eG ajg bhdg SfI EKfJjf hKdGKjf hSHYeGFI s
(3BNQgG (B:s
(3JfJgi CKfGA MhGOK SfI (B742 (3ai SdWfI GdhGKb s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B235 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B133s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B407 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B326 s
(3eUOQ GbJfGA GdCUd (B:s
(3NOGHNT HJfg (B(2337) s
Keywords: (3GdJGQjNs